Influence of Season & Months on Some Red Blood Curpusls & Some of their Parameters of She – Camels from Parturition to One Year after under Libyan grazing Conditions - Altif, Tarek Abdo – Alslam Salem (Al-Mukhtar Journal of Sciences, 2008)
The study was conducted at the middle region of Libya (El - Hisha area) on three She - camels under the desert conditions to determine the effect of season and months on red - blood curpsuls and some of their parameters (RBC, PCV, Hb, MCH, MCV , MCHC) from parturition to one year after blood samples were taken monthly except at months of March and December. The results showed that (RBC, PCV and Hb) were increased significantly (p < 0.05) during Spring , where as (MCV) was increased significantly (p < 0.05) through Winter and Summer. There were no significant differences between seasons for (MCH). During mating season, (RBC, PCV and MCV) were increased significantly (p <0.05). At parturition (MCV) and (MCH) increased significantly (p < 0.05). During the first month after the parturition (Hb, MCH, MCV, MCHC) were decreased significantly (p < 0.05) because of starting milk production. Through the third month (RBC) incre-ased but (MCV) decreased significantly (p < 0.05). (MCHC) increased but (PCV) decreased significantly (p < 0.05) during the eighth month.